(3GdeVGQHI ceG JLQjgG GdeUGQa GdGSdGejI h JWHjbGJgG GdeYGUQI (B/s - (3MeOGf, YHO GdeWdH YHO GdQRGbs ((3GdGScfOQjI(B: s (3OGQ GdacQ GdLGeYj(B, s, 2005)
(3eaghe GdeVGQHI h OdjdgG h MceI TQhYjJgG h WHjYJgG(B, (3CbSGegG h GdGdaGX GdJj JfYbO HgG h cPG GQcGf h GMcGe GdeVGQHI GVGaI Gdi GNJdGa GdeVGQH h QH GdeGd h aj GdGNjQ eHWdGJ GdeVGQHI(B.s
(3eQGLY U(B.152s
Keywords: (3eUGQa GSdGejIs; (3eVGQHIs